CREATION OF LOCAL MICROORGANISMS (MOLES) WITH THE USE OF HOUSEHOLD VEGETABLE WASTE AS A STARTER/DECOMPOSER FOR COMPOST FERTILIZER MAKING - Mukarramah, Cut; Harunsyah, H; Nahar, N (Jurnal Sains dan Teknologi Reaksi, 2024)
ABSTRACTLocal Microorganisms (MOL) are microorganisms made from natural materials as a medium for the development of microorganisms that are useful for accelerating the destruction/decomposition of organic matter (the process of decomposition into compost/organic fertilizer). In addition, it can also function as additional nutrients for plants, Local Microorganisms contain macro and micro nutrients and also contain microbes that have the potential to be a catalyst for organic matter, growth stimulants and as plant disease pest control agents. Based on the content contained in the MOL, MOL can be used as a decomposer, biofertilizer, and as an organic pesticide. This type of research is an experiment, by making a formulation of MOL solution based on the content/concentration of coconut water in the MOL solution, the bacterial content in the sample based on laboratory testing of Samples 1.2 and 3 with values (3.57 x 106 CFU/ml, 3.86 x 106 CFU/ml and 3.94 x 106 CFU/ml). The purpose of making the formulation of MOL solution in this study is to see the effectiveness of local microorganisms (MOL) in accelerating/shortening the time of the decomposition process of organic waste in making compost, the fastest decomposition value/time in samples 1-4 with the amount of stsrter/decomposer solution used 1 liter requires a decomposition time of 5 weeks.Keywords: Local Microorganisms, Starter/Decomposer, Compost Fertilizer